Kierkegaard - Tsakiri, V. author. aut Link
XII, 203 p.
Keywords: This work uses the writings of Kierkegaard to offer a novel and challenging way of approaching the concepts of anxiety, repetition, freedom and contemporaneity. Pivotal to this project is a reinterpretation of Kierkegaard's notion of 'taking notice' and its elevation to the status of a central principle which opens up new interpretive dimensions.